Marital Satisfaction in Adolescent Women with Premarital Pregnancy Seen from the First 5 Years of Marriage - Bessie, Valentina Henderina; Anakaka, Dian Lestari; Mage, Mernon Yerlinda Carlista; Berek, Noorce Christiani (Journal of Health and Behavioral Science, 2024)
This research examines marital satisfaction among young women with premarital pregnancy in Kupang City in the first five years of marriage. The method of research used​ is a qualitative study. Data collection was carried out with technique interview use guidelines interview and coding in the results interview. The subjects in this study were chosen based on specific criteria using purposive sampling. The respondents are four female adolescents aged 17-22 who have undergone a wedding for five years. Results from this study show that a woman who married at an adolescent age feels satisfaction in their marriage and is capable of adapting to build harmony in the family.